Classification of Megathyrsus Maximus Accessions Grown in the Colombian Dry Tropical Forest by Nutritional Assessment During Contrasting Seasons - Carvajal-Tapia, Juliana Isabel; Mazabel, Johanna; Vivas-Quila, Nelson Jose (Frontiers in Sustainable Food Systems, 2021)
The diversity and use of tropical forages for cattle feeding are the protagonists in livestock systems. The production and nutritional quality of forages represent a strategy of continuous research in animal feeding to help mitigate the environmental impact generated by tropical livestock. The objective of this study was to classify the nutritional behavior in contrasting seasons and the relationship with agronomic traits of a collection of 129 CIAT (Centro Internacional de Agricultura Tropical) accessions of Megathyrsus Maximus established in the Colombian dry tropics. By means of the near-infrared reflectance spectroscopy (NIRS) technique, crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), and in vitro dry matter digestibility (IVDMD) were determined under rainy and dry seasons as fixed effects. We measured plant height, dry matter biomass (DMB) and flowering in field. Aspects such as plant height and DMB did not show correlation with nutritional aspects, whereas flowering was correlated with the content of structural carbohydrates. Despite genotype and precipitation affecting nutritional value, there is relative nutritional steadiness in NDF, ADF, and IVDMD between seasons for some accessions. According to the cluster analysis carried out for each season, it was evidenced that from the total collection, 51.2% of the accessions during the dry season and 19.4% of the accessions during the rainy season were classified with a better nutritional profile, thus, showing a higher number of materials with better nutritional behavior in the dry season. Both the genotypic characteristics of M. maximus and environmental conditions during contrasting seasons are factors that might influence the variability of the nutritional content, productive parameters, and flowering. Additionally, fodder material classification under Hotelling's T-squared test and Nutritional Classification Index suggests accessions that might be promising for resilient nutritional quality and adequate DMB, which proves that M. maximus could become an alternative for animal feeding and sustainable livestock production during critical dry periods in tropical agroecosystems.